The Impact of Macroeconomics Factors on Non-Performing Loans : A Case Study of KBMI IV Banks - Id'risa, Nevia; Al Muizzuddin Fazaalloh (Contemporary Studies in Economic, Finance and Banking, 2026)
This study is grounded in the urgency of maintaining banking system stability, particularly among KBMI IV banks, which play a dominant role in Indonesia’s financial system, amid macroeconomic fluctuations that may increase the Non-Performing Loan (NPL) ratio. The research aims to examine the effects of inflation, economic growth, exchange rates, interest rates, and the Loan to Deposit Ratio (LDR) on the NPLs of KBMI IV banks during the 2016–2023 period. This study employs a quantitative approach using the Error Correction Model (ECM) to analyze both short-term and long-term relationships based on secondary data derived from published banking financial reports and macroeconomic statistics. The findings indicate that, in the long run, exchange rates, interest rates, and LDR significantly affect NPLs, while inflation and economic growth do not; in the short run, only exchange rates and interest rates have a significant impact. These results highlight the importance of strengthening credit risk management, ensuring efficient fund allocation, and adopting adaptive policy responses to macroeconomic dynamics in order to maintain credit portfolio quality and financial stability.